Role of social capital and self-efficacy as determinants of stress in pregnancy - Hajar Pasha; Mahbobeh Faramarzi; Mohammad Chehrazi; Maria Esfandyari; Shiva Shafierizi (Tzu Chi Medical Journal)
Objectives: The study investigated the role of social capital, self-efficacy, and depression as determinants of stress during pregnancy. Materials and Methods: In a cross-sectional study, 200 low-risk pregnant women with at least 5 years of education and ages 18 or more were enrolled in public obstetric clinics of Babol University of Medical Sciences. The participants completed four questionnaires including Social Capital, Revised Prenatal Distress Questionnaire (NuPDQ), Perceived Stress, and General Self-efficacy. Results: Women at late phase of pregnancy had lower mean scores of total social capital (61.5 ± 17.1 vs. 47.1 ± 18.1) and self-efficacy (60.1 ± 9.7 vs. 55.1 ± 15.2) compared to those at early pregnancy. Social capital was the negative independent variable associated with pregnancy-specific stress in the adjusted model (β = −0.418, P = 0.020). Both social capital (β = −0.563, P ≤ 0.001) and self-efficacy (β = −0.330, P ≤ 0.001) were negative independent variables associated with general stress. Conclusions: Our findings suggest that health professionals should note the benefits of social capital in stress management and encourage women in establishing stronger relations and neighborhood environments during pregnancy.